2018
DOI: 10.1093/sleep/zsx201
|View full text |Cite
|
Sign up to set email alerts
|

Changing Faces of Obstructive Sleep Apnea: Treatment Effects by Cluster Designation in the Icelandic Sleep Apnea Cohort

Abstract: OSA treatment response patterns differed by initial clinical phenotype and PAP adherence. Individuals with insomnia-related symptoms may require additional targeted therapy for these complaints. These findings underscore the need for a personalized approach to management that recognizes patients with a range of OSA presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 41 publications
3
93
0
2
Order By: Relevance
“…[40]. Between 2013 and 2018, a number of large cluster analyses of OSA samples also identified that 32%-54% of OSA patients indicate symptoms of 'disturbed sleep', characterized by nocturnal insomnia symptoms, more frequent use of sedative-hypnotic medications, and lower use of CPAP therapy [26,27,41,42]. Most recently, Zhang and colleagues conducted a systematic review and meta-analysis including 37 studies investigating the co-morbidity of insomnia and OSA, and reported that 35% of insomnia patients have an AHI of ≥5, and 29% have an AHI of ≥15, while 38% of OSA patients meet insomnia criteria [43].…”
Section: Comisa Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…[40]. Between 2013 and 2018, a number of large cluster analyses of OSA samples also identified that 32%-54% of OSA patients indicate symptoms of 'disturbed sleep', characterized by nocturnal insomnia symptoms, more frequent use of sedative-hypnotic medications, and lower use of CPAP therapy [26,27,41,42]. Most recently, Zhang and colleagues conducted a systematic review and meta-analysis including 37 studies investigating the co-morbidity of insomnia and OSA, and reported that 35% of insomnia patients have an AHI of ≥5, and 29% have an AHI of ≥15, while 38% of OSA patients meet insomnia criteria [43].…”
Section: Comisa Prevalencementioning
confidence: 99%
“…Barthlen and colleagues were among the first to describe the association of insomnia symptoms and reduced CPAP adherence among two patients with severe OSA and insomnia symptoms [68]. Since this time, a large number of case studies [69], pilot studies [70,71], chart-reviews [65,72], treatment trials [44,49,50], and cluster analyses [41,42] have examined the effect of co-morbid insomnia symptoms on reduced CPAP outcomes in OSA patients. Although some studies report no association [63,73,74], the majority of research suggests that the presence of insomnia symptoms reduces CPAP acceptance and use.…”
Section: Traditional Treatment Approachesmentioning
confidence: 99%
“…It is challenging to speculate why the early quitters also reported reduced nasal obstruction. However, it has been shown recently that there is a decrease in symptoms in general, even amongst non‐users to some extent (Pien et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last several decades, we have witnessed substantial increases in the granularity of the morbid phenotype of OSA, and such observations have prompted us to rethink some of the stricter early concepts. Among them, rather than viewing OSA as a single disease model that is applicable to all patients, we have formulated the conceptual framework of distinct phenotypes of OSA that may be driven by different mechanisms, link to different clinical manifestations, and display divergent responses to therapy [1][2][3][4][5][6]. In this contextual setting, the aspirational goals of the field are to first and foremost identify those OSA patients likely to benefit from treatment and administer the correct intervention, i.e.…”
mentioning
confidence: 99%